1.6q-3.5-5.2q=-4.6q-5.4

Simple and best practice solution for 1.6q-3.5-5.2q=-4.6q-5.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.6q-3.5-5.2q=-4.6q-5.4 equation:


Simplifying
1.6q + -3.5 + -5.2q = -4.6q + -5.4

Reorder the terms:
-3.5 + 1.6q + -5.2q = -4.6q + -5.4

Combine like terms: 1.6q + -5.2q = -3.6q
-3.5 + -3.6q = -4.6q + -5.4

Reorder the terms:
-3.5 + -3.6q = -5.4 + -4.6q

Solving
-3.5 + -3.6q = -5.4 + -4.6q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '4.6q' to each side of the equation.
-3.5 + -3.6q + 4.6q = -5.4 + -4.6q + 4.6q

Combine like terms: -3.6q + 4.6q = 1q
-3.5 + 1q = -5.4 + -4.6q + 4.6q

Combine like terms: -4.6q + 4.6q = 0.0
-3.5 + 1q = -5.4 + 0.0
-3.5 + 1q = -5.4

Add '3.5' to each side of the equation.
-3.5 + 3.5 + 1q = -5.4 + 3.5

Combine like terms: -3.5 + 3.5 = 0.0
0.0 + 1q = -5.4 + 3.5
1q = -5.4 + 3.5

Combine like terms: -5.4 + 3.5 = -1.9
1q = -1.9

Divide each side by '1'.
q = -1.9

Simplifying
q = -1.9

See similar equations:

| 4x+10=x+3(3x+3)+1 | | 12x^2+41x+24=0 | | 5x+29y=-19 | | 2(n+2)=3n+9 | | x*6+47=x*11-8 | | x^3-70x^2+1500x-10800=0 | | 5(y-1)=7(3+y) | | 18x^2-9x-20=0 | | b^2+3=5b-3 | | 58-6x=3x+19 | | x^2+36=100 | | 8-2a=2 | | -3-2(y+4)=3y-(4y-5) | | 12x^2+43x+36=0 | | 5(2x+n)=2(n-1) | | 47=-62 | | 10x+6x= | | 29+18=-59-3 | | 3x=5y+2 | | 3(2x-1)=11-x | | 4y-4=6-7y | | 18x-3=51 | | 18y=15(y-8) | | -4x-12=13+x | | 5m+8-2m=17+4m-3 | | 5y=x+17 | | 6m-12m=1-4 | | 40x+780=70x+1230 | | 8y-6(3y-7)=0 | | 81^-3/4 | | 20x+800=50x+1250 | | 20x+80=50x+1250 |

Equations solver categories